Aflatoxin M1 and Shelf life Analysis of Goat and Cow Milk Samples - Jyoti; Singh, Namita Ashish (Indian Journal of Dairy Science, 2024)
Due to its medicinal benefits in mouth ulcers, dengue fever, etc. raw goat milk is widely used but ingestion of raw goat milk may have severe side effects. Aflatoxins M1 is produced by Aspergillus species and under long-term exposure, these are mutagenic, genotoxic, and carcinogenic. This study examined the shelf life of raw goat and cow milk at different storage temperatures (including ambient temperature, 5°C, and -19°C), via analysis of microbiological quality by standard plate count method. Incidence of aflatoxin M1 was also studied in raw goat and cow milk samples by lateral flow system. Cow milk showed a shelf life of 12 days while goat milk had up to 48 days at 5℃. The total viable count, coliform count, and spore count of goat milk were reported 5.89 log cfu/mL 2.80 log cfu/ml, and 2.3 log cfu/ml in 75 days of storage while in cow milk samples it was 7.93 log cfu/ml, 5.64log cfu/ml and 3.6 log cfu/ml, respectively in 45 days at -19℃. All the goat milk samples were found negligible for Aflatoxin M1 while cow milk samples showed a 40% incidence at 0.5 ppb. Our study showed that the quality of goat milk is commendable compared to cow milk in terms of aflatoxin M1 and bacterial count but due to less production and other factors goat milk is not widely used at the commercial level.